Hydromagnetic rarefied fluid flow over a wedge in the presence of surface slip and thermal radiation - Das, Kalidas; Sharma, Ramprakash; Duari, Pinaki Ranjan (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is presented to investigate the effects of thermal radiation on a convective slip flow of an electrically conducting slightly rarefied fluid, having temperature dependent fluid properties, over a wedge with a thermal jump at the surface of the boundary in the presence of a transverse magnetic field.
Keywords: convective flow; heat transfer; surface slip; magnetic field; thermal radiation